Critical agitation for microcarrier suspension in orbital shaken bioreactors: Experimental study and dimensional analysis. (27th January 2015) - Olmos, Eric; Loubiere, Karine; Martin, Céline; Delaplace, Guillaume; Marc, Annie
Abstract: Orbital shaken bioreactors are widely used at the laboratory scale for the culture of animal cells in suspension mode. In the case of adherent-dependent cell lines, the choice of agitation conditions at which all particles are just-suspended (or attain complete suspension) has often to be determined. Indeed, with orbital shaken bioreactors, this choice results from the combination of two parameters: the orbital diameter and the agitation rate. That is why, a new experimental protocol for the determination of critical agitation conditions for microcarrier complete suspension has been developed in this paper. It consisted in a side-view visualization of blue-stained particles in shaken Erlenmeyer flasks and cylindrical flasks. 220 experiments representative of animal cell culture conditions have been carried out to study the effect of various operating conditions (bioreactor size and geometry, particle type, density and diameter, liquid viscosity, shaking diameter, filling ratio). Furthermore, a dimensional analysis has been performed, leading to a correlation relating a Froude number (in which the critical agitation N c for complete particle suspension is embedded) to four other dimensionless numbers. Then, the critical agitation conditions determined in this paper were analyzed and discussed with respect to the data available in the literature on the flow structure occurring inside the flask. Our findings revealed that high orbital shaking diameters and large cylindrical vessels should be promoted to get microcarriers into suspension at a minimized power dissipation per unit of volume. Abstract : Highlights: Experimental characterization of particle suspension in orbital shakers. New correlation predicting critical agitation conditions for complete particle suspension. Larger orbital diameters promote smaller power dissipations at complete particle suspension.